Undernutrition when young and the risk of poor renal function in adulthood in women with diabetes in Shanghai, China - Qin, Qiaojing; Chang, Kaili; Wu, Qing; Fan, Weifeng; Gu, Yong; Niu, Jianying; Liu, Xueguang (Journal of international medical research, 2021)
Objective To evaluate the effect of undernutrition when young on the risk of poor renal function in adulthood in women with diabetes mellitus. Methods We studied diabetic women born between 1921 and 1958 who were exposed to the 1959-to-1962 Chinese famine when they were 0 to 37 years old. Exposure age was classified as young adulthood (18 to 37 years), adolescence (10 to 17 years), or childhood (0 to 9 years). The Adolescence group, which was provided with the largest amount of food during the famine, was used as the control group, and variance and binary logistic regression analyses were performed. Results The prevalences of low estimated glomerular filtration rate (eGFR) in the Childhood, Adolescence, and Young adulthood groups were 5.26%, 22.39%, and 79.24%, respectively. The risk of low eGFR for the Young adulthood group (odds ratio [OR] 1.65, 95% confidence interval [CI] 1.10, 2.48), but not for the Childhood group (OR 1.10, 95% CI 0.68, 1.78), was higher than that for the Adolescence group after adjustment for potential confounders. Conclusions Undernutrition during young adulthood significantly increases the risk of renal dysfunction in adult women with diabetes. Therefore, the nutrition of less affluent young women should be improved.